2015
DOI: 10.1007/s13762-015-0790-5
|View full text |Cite
|
Sign up to set email alerts
|

Environmental pollutants leading to carcinogenesis: process of natural selection of human cells due to chronic inflammation and sustained stress environment

Abstract: Epidemiological studies have shown that 70-90 % of all cancers are caused due to the chemicals present in environment. Exogenous exposure to carcinogens and their interaction with genetic sequences and endogenous factors, like exposures to products of metabolism which lead to acute stress, disruption of hormones and inflammation of tissues, are triggering factors. Due to relatively small risk of cancer following immediate exposure, the precise quantification of the burden of human cancer attributed to environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…On the basis of this classification, environmental contaminants represent one of the main contributors to tumor initiation, as abundantly documented by the increasing number of research studies during the past decade [ 36 ]. The list of chemical agents catalogued as carcinogenic includes the different conformers of hexachlorocyclohexane, among which stands out the well-known pesticide Lindane (γ-HCH) [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of this classification, environmental contaminants represent one of the main contributors to tumor initiation, as abundantly documented by the increasing number of research studies during the past decade [ 36 ]. The list of chemical agents catalogued as carcinogenic includes the different conformers of hexachlorocyclohexane, among which stands out the well-known pesticide Lindane (γ-HCH) [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Organic herbicides (amide compounds) are more toxic to animals. Haemolysis, methemoglobinemia and immunotoxicity have occurred on experimental exposure [39].…”
Section: Herbicidesmentioning
confidence: 99%
“…Lung cancer has been the most common cancer and the leading cause of cancer-related death among all patients worldwide [1]. Epidemiological studies have found that more than 80% of human lung cancers are closely related to human exposure to chemical carcinogens in living and working environments [2,3].…”
Section: Backgroudmentioning
confidence: 99%